2014 Ninth International Conference on P2P, Parallel, Grid, Cloud and Internet Computing 2014
DOI: 10.1109/3pgcic.2014.73
|View full text |Cite
|
Sign up to set email alerts
|

An Enhancement for Key Management in LTE/SAE X2 Handover Based on Ciphering Key Parameters

Abstract: The security of handover key management in Long Term Evolution(LTE)/System Architecture Evolution(SAE) has been a popular topic in recent years. In this paper we first describe the security architecture and key hierarchy of LTE/SAE, clarifying security requirements of key management in handover. Next, we analyze security of key management in X2 handover(intra-MME handover), and point out the current key management mechanism in X2 handover only satisfy two-hops forward security and one-hop backward security, bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 3 publications
0
9
0
Order By: Relevance
“…T U , or the MRI, i.e. T R , increases (see Lemmas 1,2,3 and 4). In other words, either a short and frequent KUI or a short MRI causes a waste of signalling overhead, but helps reduce the risk of security breaches with small NEP and OPV.…”
Section: Boundary-based Fractional Programming For Optimising Kui mentioning
confidence: 94%
See 1 more Smart Citation
“…T U , or the MRI, i.e. T R , increases (see Lemmas 1,2,3 and 4). In other words, either a short and frequent KUI or a short MRI causes a waste of signalling overhead, but helps reduce the risk of security breaches with small NEP and OPV.…”
Section: Boundary-based Fractional Programming For Optimising Kui mentioning
confidence: 94%
“…[8], [13], [14]. 2 To that end, a mathematical model was developed in [8] to represent the average Number of Exposed Packets (NEP) between two root key updates and the average value of Signaling Overhead Rate (SOR). 3 It was shown that the security of intra-MME handovers can be enhanced by minimising the NEP so as to eliminate the desynchronisation attacks.…”
Section: Introductionmentioning
confidence: 99%
“…This loophole has been presented in some recent works [3][4], proposing some solutions to overcome the de-synchronization attack [5][6][7][8], but those could not completely prevent the attack or the proposed solutions were infeasible to implement. Therefore, proposing other solutions to prevent this attack and to maintain the forward key separation during the HO procedure is still needed.…”
Section: Introductionmentioning
confidence: 99%
“…In the intra MME handover, i.e. when a user equipment (UE) moves from a source to a target eNodeB 1 within the same MME, the source eNodeB provides the target eNodeB with a new session key 2 to be used after handover. The new key is generated from the current one by either utilising a one-way function, a.k.a.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, attacker can either decipher the communications between a genuine eNodeB and a UE or compromise all future keys between 1 A node/access-point provides all radio access protocols. 2 Session keys are used to encrypted messages, i.e. user data and signaling packets, exchanged between a UE and its serving eNodeB [4].…”
Section: Introductionmentioning
confidence: 99%